The Efficacy of Channa Striata Extract Administration in Improving Albumin and Creatinine Levels in Sepsis Patients in the Intensive Care Unit - Panggabean, Mathilda; Lubis, Andriamuri Primaputra; Irina, Rr. Sinta; Amelia, Rina (Indonesian Journal of Applied Research (IJAR), 2024)
Albumin levels in the blood are an indicator for assessing the severity of sepsis. In sepsis patients, administering albumin extract from Channa striata has better potential to replace Human Albumin by 20%. This study aims to determine the role of Channa striata extract (CSE) in improving albumin and creatinine in sepsis patients. This research is a quasi-experimental research with a pre-post-test design. Sepsis patients who meet the inclusion and exclusion criteria and sign the informed consent form will be divided into treatment and control groups. Both groups received the same therapy protocol, except for the treatment group, which will be given CSE at a dose of 5gr, three times a day, for five days. Albumin, creatinine, and SOFA score measurements will be taken before the treatment and on the 7th day. All data will be tabulated and analyzed using statistical software. This study consisted of 2 groups, with a sample size of 20 patients for each group. It was found that the mean age of the research sample was 56.1 + 11.8 years. In the treatment group, there was no decrease in albumin levels before and after (2.76 + 0.41 to 2.76 + 0.40), p=0.952. There was no significant difference in assessing creatinine levels before and after treatment, p>0.05. There was an increase in SOFA score before and after treatment in both groups, p<0.05. Channa striata extract is clinically significant for improving the condition of sepsis patients in the ICU.